WHAT IS HAPPENING IN THIS CLASS?: KAJIAN PSIKOSOSIAL SITUASI DI DALAM KELAS MELALUI PERSPEKTIF GENDER - Hallaby, Syarifah Fadiya; Hamama, Syarifah Farissi (Jurnal Pendidikan Almuslim, 2017)
The aim of this study was to investigate the differences between male and female students’ perception on the classroom environment.  This study was conducted at SMU Negeri 4 Banda Aceh with a total of 103 students, consist of 50 male students and 53 female students. Students’ perception was collected by using ‘What is Happening in This Class?’ (WIHIC) questioner. The Independent T-Test was used to analysethe collected data.The results showed that there were no differences between male and female perception on actual classroom environment. However,differences were found on student involvement preferred score. The male students’ preferred score was significantly higher than the female students’. This finding indicated that both male and female student preferred to be more involved in class, but the level of involvement that the male students wish for was higher than the female students’. Key Words: WIHIC, gender, classroom environment